2007
DOI: 10.1182/blood-2006-07-036210
|View full text |Cite
|
Sign up to set email alerts
|

Human IL4I1 is a secreted l-phenylalanine oxidase expressed by mature dendritic cells that inhibits T-lymphocyte proliferation

Abstract: Interleukin-4-induced gene 1 (IL4I1) was first described as a B-cell IL4-inducible gene and is highly expressed in primary mediastinal B-cell lymphomas. We established stable HEK293 clones expressing human and mouse IL4I1 to examine their biochemical properties and function. Both proteins were secreted into the culture medium, and we observed the secretion of endogenous human IL4I1 (hIL4I1) protein in a mediastinal lymphoma B-cell line, MedB-1. We showed that IL4I1 has L-amino acid oxidase activity, optimal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(202 citation statements)
references
References 30 publications
12
177
0
Order By: Relevance
“…IL4I1 encodes a secreted L-amino-acid oxidase that inhibits human T lymphocyte proliferation in vitro by inducing a temporary decrease in CD3z chain expression resulting from the enzymatic production of H 2 O 2 (Boulland et al, 2007). We found that IL4I1 mRNA expression was virtually undetectable on either resting or activated Th1 cell clones, but it was highly expressed on resting Th17 cell clones and further increased by anti-CD3-CD28 stimulation ( Figure 4A).…”
Section: Upregulation Of Il4i1 Expression In Th17 Cells and In Their mentioning
confidence: 73%
See 1 more Smart Citation
“…IL4I1 encodes a secreted L-amino-acid oxidase that inhibits human T lymphocyte proliferation in vitro by inducing a temporary decrease in CD3z chain expression resulting from the enzymatic production of H 2 O 2 (Boulland et al, 2007). We found that IL4I1 mRNA expression was virtually undetectable on either resting or activated Th1 cell clones, but it was highly expressed on resting Th17 cell clones and further increased by anti-CD3-CD28 stimulation ( Figure 4A).…”
Section: Upregulation Of Il4i1 Expression In Th17 Cells and In Their mentioning
confidence: 73%
“…Whereas the reduced IL-2 responsiveness was explained by the lack of PI3K-AKT-mTORC1 axis activation, the defective IL-2 production by Th17 cells appeared to be related to their reduced c-Fos, c-Jun, and nuclear factor of activated T cells (NF-AT) activity. The reduced activity of these transcription factors associated with high expression of the IL-4-induced gene 1 (IL4I1) mRNA, which encodes for a L-phenylalanine oxidase that has been shown to downregulate CD3z expression in T cells (Boulland et al, 2007). IL4I1 mRNA expression was strictly RORC dependent and was already detectable in Th17 cell precursors from UBC and newborn thymus.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, we have observed high IL4I1 expression in antigen-presenting cells of myeloid origin (macrophages and dendritic cells) from normal and inflammatory lymphoid tissue. 2 These observations highlight similarities between IL4I1 and other amino-acid-catabolizing enzymes, such as indoleamine-2,3-dioxygenase (IDO), arginase-1 and inducible nitric oxide synthase, all associated with the inhibition of T-cell responses. The expression of these enzymes has been demonstrated in several tumor types, both in the malignant cell and/or the microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of potential substrates for this enzyme demonstrated that it was optimally active following exposure to the aromatic amino acids phenylalanine and tryptophan (Fig. 2) in keeping with the known activity of this enzyme in the immune system (Boulland et al 2007). The localization of this enzyme in the sperm acrosome is also consistent with the observation that this enzyme is maximally active at acidic pH and is preferentially targeted to lysosomes (Mason et al 2004); the acrosomal vesicle is known to exhibit a low intraacrosomal pH and shares many features with cellular lysosomes (Working & Meizel 1983, Moreno & Alvarado 2006.…”
Section: Discussionmentioning
confidence: 99%